Análise comparativa de vinculações rígidas e semirrígidas no dimensionamento estrutural em concreto armado utilizando o software TQS - Zilio, Érica (2025)
This study presents a comparative analysis of the use of rigid and semi-rigid connections in the structural design of a four-story reinforced concrete building, using the TQS software. With technological advancements favoring the use of computational tools in the construction industry, structural behavior can be represented as closely as possible to reality. Generally, structural designs adopt rigid connections, where the total transmission of bending moments occurs. However, after the building is constructed, the rigidity of the connections between elements cannot be fully guaranteed. This introduces the concept of semi-rigid connections, which involve reducing the fixed-end capacity of these connections, directly influencing the distribution of forces, displacements, and the overall stability of the building. The objectives include designing the same structure using rigid connections in one scenario and semi-rigid connections in another, analyzing the differences in the structural behavior of the elements, overall stability, and material consumption. The methodology employed was exploratory in nature, involving structural design using both connection types in the TQS software, with a qualitative and quantitative approach based on theoretical foundations and structural design. The results indicate that semi-rigid connections tend to present lower values for negative bending moments and higher values for positive bending moments when compared to rigid connections. These changes led to a reduction of 2,0% in steel consumption and affected the building's overall stability by increasing stability parameters. Finally, the analysis demonstrated that the choice of connections has a direct impact on structural behavior, influencing the forces acting on structural elements, material consumption, and the building's overall stability. It also reinforces the importance of a careful approach to the use of computational models and the definition of design parameters.